Law and war - Sarat, Austin; Douglas, Lawrence; Umphrey, Martha Merrill (Amherst series in law, jurisprudence, and social thought., 2014)
This work explores the cultural, historical, spatial, and theoretical dimensions of the relationship between law and war - a connection that has long vexed the jurisprudential imagination. Law has emerged as a force that stands over and above war, endowed with the power to authorise and restrain, to declare and limit, to justify and condemn.